Developing Augmented Reality E-Comic Based on Baduy Folklore for English Literacy Enhancement - Ardianto, Teguh; Fariji, Irvan; Subekhi, Andri Imam; Kusmana, Nandang; Junaedi, Yusup (Journal of Language and Literature Studies, 2026)
In the context of education, literacy is no longer understood merely as the ability to read and write. It also includes the capacity to understand texts, interpret meaning, evaluate information critically, communicate ideas effectively, and apply knowledge to solve real-life problems. Therefore, this study aims to develop an Augmented Reality (AR)-based E-Comic by integrating Baduy folklore, meeting the criteria of validity, practicality, and effectiveness in optimizing English literacy skills. This study employs Research and Development (R&D) approached to create and evaluate an educational product. It follows the ADDIE model, which consists of five systematic stages: Analyze, Design, Development, Implementation, and Evaluation. The development of this E-Comic is designed to provide a contextual learning experience supported by dynamic and interactive 3D visualizations, thereby enhancing students’ literacy skills, particularly in English. The findings indicate that the developed AR-based e-comic was positively received by students and is suitable for use as teaching material in English language learning. This is consistent with other studies indicating that e-comics improve learning comprehension and are highly relevant as teaching media. This is also consistent with the results from utilizing digital teaching materials as an alternative for English classes. The average score from media experts reached 91.3%, while student responses averaged 84%, both categorized as highly feasible. Therefore, the product can be effectively implemented as a teaching material for English language learning.